Measurement of charged current deep inelastic scattering cross sections with a longitudinally polarised electron beam at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
Measurements of the cross sections for charged current deep inelastic scattering in e - p collisions with longitudinally polarised electron beams are presented. The measurements are based on a data sample with an integrated luminosity of 175 pb-1 collected with the ZEUS detector at HERA at a centre-of-mass energy of 318 GeV. The total cross section is given for positively and negatively polarised electron beams. The differential cross-sections d σ/dQ 2, d σ/dx and d σ/dy are presented for Q 2>200 GeV2. The double-differential cross-section d 2 σ/dxdQ 2 is presented in the kinematic range 280